ACTION OF HINDU COMMUNITY IN DEVELOPING INTERNATIONAL RELATIONSHIP THROUGH CULTURAL TOURISM IN SENGGIGI BEACH - I Gusti Komang Kembarawan (IAHN-TP Palangka Raya, 2019)
This study aims to conduct a study of the actions of Hindus in building International relations through the development of cultural tourism in Senggigi beach. The phenomenon is to maintain the sanctity of the temple associated with the development of tourism in Senggigi beach. There are three focuses on the research, namely the challenges faced by Hindus in preserving the existence of the Segara Temple during tourism development, the impact of tourism development on the sanctity of the Segara Temple, the actions of Hindus in conserving the sanctity of Segara Temple. This study was designed in the form of a qualitative descriptive study to describe the actions taken to always be able to maintain the sanctity of the temple during the rapid development of tourism. Based on this research, it was found that the challenge of Hindus in preserving the existence of the Segara Temple was the tendency for a decline in the sanctity of the temple due to the tourists visiting the temple area whose condition of the temple and tourism development distance to the Segara Temple began to be violated. The impact of tourism development on the sanctity of the Segara Temple in a positive dimension helps to finance temple activities, both the preservation of temples and the implementation of Hindu ceremonies. The negative impact is a decrease in the level of sanctity of the temple, especially tourists visiting the temple in a state of cuntaka (Unholy conditions oThe actions of Hindus in conserving the sanctity of Pura Segara through awareness of Hindus to always maintain the sanctity of the temple in all its activities, set limits on the sanctity of the temple area, communicate with tourism actors related to the sanctity of the temple, and convey to the relevant parties to respect Hindu religious ceremony activities.